Myometrial cytokines and their role in the onset of labour. Issue 3 (December 2016) - Sivarajasingam, S P; Imami, N; Johnson, M R
Abstract : Human labour is an inflammatory event, physiologically driven by an interaction between hormonal and mechanical factors and pathologically associated with infection, bleeding and excessive uterine stretch. The initiation and communicators of inflammation is still not completely understood; however, a key role for cytokines has been implicated. We summarise the current understanding of the nature and role of cytokines, chemokines and hormones and their involvement in signalling within the myometrium particularly during labour.